The technique of “voicing cartoons” as a means of developing the linguistic abilities of schoolchildren - Kulakova, Natalia V.; Vekkeser, Maria V.; Shmulskaya, Larisa S.; Zyrianova, Olga N. (BELT - Brazilian English Language Teaching Journal, 2022)
The article discusses one of the most important problems of modern primary school – the development of linguistic abilities of students. The choice of the research topic is due to the fact that linguistic abilities are one of the key components of successful language education and instruction in general. The purpose of this paper is to reflect upon the level of development of linguistic abilities of primary school children and to present the method of using the technique “scoring (voicing) of cartoons” (dubbing is the process of video sound accompaniment, carried out separately from image shooting), contributing to the development of these abilities. To solve this problem, the following methods were used: an analysis of pedagogical and linguistic-methodical sources, a comparative analysis, generalization of pedagogical and linguistic-methodical data obtained in the study of primary sources. In this paper, we will consider the possibilities of using the technique of “scoring of a cartoon”, aimed at improving the linguistic abilities of younger students (age of children - 9 years, students 3 grade; study English for the second year). The results of the experimental work confirm the hypothesis and indicate that the use of scoring of videos will contribute to a more effective development of linguistic abilities of younger students.